Physical Therapy Effectiveness - Bernardo-Filho, Mario; Cunha de Sá-Caputo, Danúbiada; Taiar, Redha (IntechOpen, 2020)
Physical therapy involves non-pharmacological interventions in the management of various clinical conditions. It is important to highlight the physical therapy procedures that are suitable, effective and, in general, do not have side effects or complications when properly performed. Physical therapy can be valuable in different situations along of the various steps of human development and in various clinical disorders. Indeed, topics on different approaches have been included in this book, which makes this book useful for readers to improve their professional performance.